Fixed frequency finite-state model predictive control for indirect matrix converters with optimal switching pattern - Lei, Jiaxing; Tariscotti, Luca; Trentin, Andrew; Zanchetta, Pericle; Wheeler, Patrick; Formentini, Andrea (2016)
Finite States Model Predictive Control (MPC) has been recently applied to several converters topologies for the many advantages it can provide such as fast dynamics, multi-target control capabilities, easy implementation on digital control board and capability of including constraints in the control law. However, its variable switching frequency and lower steady state waveform quality, with respect to standard control plus modulator systems, represents a limitation to its applicability. Modulated Model Predictive Control (M²PC) combines all the advantages of the simple concept of MPC together with the fixed switching frequency characteristic of PWM algorithms. In particular this work focuses on the Indirect Matrix Converter (IMC), where the tight coupling between rectifier stage and inverter stage has to be taken into account in the M²PC design. This paper proposes an M²PC solution, suitable for IMC, with an optimal switching pattern to emulate the desired waveform quality features of Space Vector Modulation (SVM). In the optimal pattern, the switching sequences of the rectifier stage and inverter stage are rearranged in order to always achieve zero-current switching on the rectifier stage, thus simplifying its commutation strategy. In addition, the optimal pattern enables M²PC to produce sinusoidal source current, sinusoidal output current and maintain all desirable characteristics of MPC.